Environment‐specific modulation of odorant representations in the honeybee brain. (1st November 2016) - Chakroborty, Neloy Kumar; Menzel, Randolf; Schubert, Marco
Abstract: Ca 2+ imaging techniques were applied to investigate the neuronal behavior of projection neurons in the honeybee antennal lobe (AL) to examine the effects of long‐lasting adaptation on odorant coding. Responses to eight test odorants were measured before, during, and after an odor adaptation phase. Bees were exposed to the adapting odor for 30 min. Test odorant responses were only recorded from a sub‐population of accessible glomeruli on the AL surface. Projection neurons, the output neurons of the antennal lobes, are projecting through the lateral, mediolateral, and medial AL tract to higher centers of the olfactory pathway. Due to our staining techniques, we primarily focused our study on projection neurons going through the lateral and medial tract. Test odorants comprised compounds with different functional groups (alcohol, aldehyde, ketone, and ester) representing floral and/or pheromone odorants. Strength and discriminability between combinatorial activity patterns induced by the test odorants were quantified. In two independent experiments, we investigated one group of animals adapted to a colony odor and another adapted to a synthetic odor. Within the experimental groups, we found test odorant responses either decreased or increased in AL projection neurons. Additionally, the discriminability between test odorant patterns became less distinct in the colony odor experiment and more distinct during adaptation in the synthetic mixture experiment. These results are interpreted as odor dependent adaptation effects, increasing or decreasing response strength and discriminability by altered neural coding mechanisms in the AL neuropile. Abstract : Honeybees were presented to odor stimuli and calcium imaging responses were recorded as characteristic neuronal activity patterns of projection neurons in the antennal lobe. Background odors changed the glomerular response strength to test odorants. The background odor of a honeybee colony reduced responses to floral‐related odorants but had a lesser effect on responses to alarm pheromone‐related odorants.